2008
DOI: 10.1002/jmri.21212
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized 3He apparent diffusion coefficient MRI of the lung: Reproducibility and volume dependency in healthy volunteers and patients with emphysema

Abstract: Purpose:To measure the apparent diffusion coefficient (ADC) of hyperpolarized (HP) 3 He gas using diffusion weighted MRI in healthy volunteers and patients with emphysema and examine the reproducibility and volume dependency. Materials and Methods:A total of eight healthy volunteers and 16 patients with emphysema were examined after inhalation of HP 3 He gas mixed with nitrogen (N 2 ) during breathhold starting from functional residual capacity (FRC) in supine position. Coronal diffusion-sensitized MR images w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
72
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 22 publications
(28 reference statements)
12
72
0
Order By: Relevance
“…The findings by Diaz et al (20) demonstrated the sensitivity of ADC to small (6%-8%) changes in lung volume. The work presented herein builds on that of Diaz et al (20) by evaluating the dependence of ADC measurements on lung inflation levels at carefully controlled lung volumes between 20% and 100% of vital capacity (VC). We performed this study to evaluate effects encounters.…”
Section: Thoracic Imaging: Effect Of Lung Inflation Level On Apparentmentioning
confidence: 99%
“…The findings by Diaz et al (20) demonstrated the sensitivity of ADC to small (6%-8%) changes in lung volume. The work presented herein builds on that of Diaz et al (20) by evaluating the dependence of ADC measurements on lung inflation levels at carefully controlled lung volumes between 20% and 100% of vital capacity (VC). We performed this study to evaluate effects encounters.…”
Section: Thoracic Imaging: Effect Of Lung Inflation Level On Apparentmentioning
confidence: 99%
“…The FDA have deemed 3 He a safe contrast agent. Various studies have assessed safely of 3 He in a range of patients with a variety of conditions [131, [168][169][170][171][172][173] with no major side effects reported. Minor symptoms such as lightheadedness, cough and transient desaturation can occur, and it does mean monitoring and careful choice of subjects is important.…”
Section: Discussionmentioning
confidence: 99%
“…The fall will be less rapid if the distribution is more inhomogeneous. This is apparent in Figure 1, which shows lacunarity as a function of box size from data obtained in an earlier reproducibility study (20). The difference between the subjects with COPD with and without AAT deficiency is addressed in the ''Discussion'' section.…”
Section: Post Hoc Lacunarity Analysismentioning
confidence: 96%